Equity of PrEP uptake by race, ethnicity, sex and region in the United States in the first decade of PrEP: a population-based analysisResearch in context - Patrick S. Sullivan; Stephanie N. DuBose; Amanda D. Castel; Karen W. Hoover; Marta Juhasz; Jodie L. Guest; Gordon Le; Shamaya Whitby; Aaron J. Siegler (Elsevier, 2024)
Summary: Background: PrEP was approved for HIV prevention in the US in 2012; uptake has been slow. We describe relative equity with the PrEP Equity Ratio (PER), a ratio of PrEP-to-Need Ratios (PnRs). Methods: We used commercial pharmacy data to enumerate PrEP users by race and ethnicity, sex, and US Census region from 2012 to 2021. We report annual race and ethnicity-, sex-, and region-specific rates of PrEP use and PnR, a metric of PrEP equity, to assess trends. Findings: PrEP use increased for Black, Hispanic and White Americans from 2012 to 2021. By 2021, the rate of PrEP use per population was similar in Black and White populations but slightly lower among Hispanic populations. PnR increased from 2012 to 2021 for all races and ethnicities and regions; levels of PrEP use were inconsistent across regions and highly inequitable by race, ethnicity, and sex. In all regions, PnR was highest for White and lowest for Black people. Inequity in PrEP use by race and ethnicity, as measured by the PER, grew early after availability of PrEP and persisted at a level substantially below equitable PrEP use. Interpretation: From 2012 to 2021, PrEP use increased among Americans, but PrEP equity for Black and Hispanic Americans decreased. The US South lagged all regions in equitable PrEP use. Improved equity in PrEP use will be not only just, but also impactful on the US HIV epidemic; persons most at-risk of acquiring HIV should have the highest levels of access to PrEP. Prevention programs should be guided by PrEP equity, not PrEP equality. Funding: National Institutes of Health, Gilead Sciences.